The Effectiveness of Audiovisual Media on Learning Outcomes of Batik Motif Material Semarangan - Herlina, Herlina; Yuyarti, Yuyarti (Elementary School Teacher, 2021)
Based on the results of observation and documentation, the arts learning outcomes of the batik patterns topic were still very low. This happened because of the learning models used were not effective. The research objective was to determine the effectiveness of the discovery learning model on the arts learning outcomes of the Semarangan batik patterns topic for fifth grade students at Bina Amal Islamic-integrated Elementary School Semarang. This research was a quasi experimental research design with quantitative methods. The sampling technique used purposive sampling. This research was conducted in four meetings in each class. The data collection technique in this study used test techniques. The learning outcomes test used pretest and posttest in the form of multiple choices. The data analysis technique used in this research was preliminary data analysis including normality test and homogeneity test, the final data analysis used independent sample t-test and n gain. The results of this study indicated that the application of the discovery learning model was effective to be applied on Semarangan batik patterns in the fifth grade at Bina Amal Islamic-integrated Elementary School Semarang. This was indicated by the results of the t-test obtained tcount ttable (2,645 2.Keywords: Effectiveness, SBdP Learning Outcomes, Semarangan Batik, Audiovisual Media